2022
DOI: 10.1108/rpj-09-2020-0223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various processing parameters on the mechanical properties and dimensional accuracies of Prosopis chilensis/PES composites produced by SLS

Abstract: Purpose The range of applications of the currently available biomass selective laser sintering (SLS) parts is limited and low-quality. This study aims to demonstrate the effects of the various processing parameters on the dimensional accuracy, bending strength, tensile strength, density and impact strength of the Prosopis chilensis/polyethersulfone (PES) composites (PCPCs) that were produced by SLS. The various processing parameters are laser power, scan speed, preheating temperature, scan spacing and layer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Therefore, through combined advantages results of RH content, 10 wt % is represent the optimum ratio in this study. The comparison of dimensional accuracy between the RHPA and related biomass composite SLS parts [30][31][32][33][34] is shown in Figure 10. From the comparison in Figure 10, the RHPA parts dimensional accuracy was superior to previously reported materials of wood-plastic composites, i.e., Bamboo flour/Thermoplastic, Cellulose/polyacid composite, and PCPC.…”
Section: The Influence Of Rh Powder Content On the Properties Of The ...mentioning
confidence: 99%
“…Therefore, through combined advantages results of RH content, 10 wt % is represent the optimum ratio in this study. The comparison of dimensional accuracy between the RHPA and related biomass composite SLS parts [30][31][32][33][34] is shown in Figure 10. From the comparison in Figure 10, the RHPA parts dimensional accuracy was superior to previously reported materials of wood-plastic composites, i.e., Bamboo flour/Thermoplastic, Cellulose/polyacid composite, and PCPC.…”
Section: The Influence Of Rh Powder Content On the Properties Of The ...mentioning
confidence: 99%
“…Producing a very high accuracy and fine finish, this technology has been using in dental and jewellery industry (Son et al, 2021) Powder bed fusion either using polymer or metal powder is a technology that thermal energy to melt and fused the powder to become an object. Known as selective laser sintering (SLS) is being use for mechanical parts production due to its material strength (Li et al, 2022).…”
Section: D Printingmentioning
confidence: 99%
“…Coded as SARS-CoV-2 is a β-coronavirus which is enveloped non-segmented positive-sense Ribonucleic acid (RNA) virus (subgenus sarbecovirus, Orthocoronavirinae subfamily) (Zhu et al 2020). It was confirmed that this virus originated from bats but how it was transmitted to humans is still unknown (Li et al 2022). As of 20 July 2021, 192,190,693 cases were detected, and the death toll has reached 4,123,780.…”
Section: Introductionmentioning
confidence: 99%